Monitoring the Progression of Cell-Free Expression of Microbial Rhodopsins by Surface Enhanced IR Spectroscopy: Resolving a Branch Point for Successful/Unsuccessful Folding - Ataka, Kenichi; Baumann, Axel; Chen, Jheng-Liang; Redlich, Aoife; Heberle, Joachim; Schlesinger, Ramona (Frontiers in Molecular Biosciences, 2022)
The translocon-unassisted folding process of transmembrane domains of the microbial rhodopsins sensory rhodopsin I (HsSRI) and II (HsSRII), channelrhodopsin II (CrChR2), and bacteriorhodopsin (HsBR) during cell-free expression has been investigated by Surface-Enhanced Infrared Absorption Spectroscopy (SEIRAS). Up to now, only a limited number of rhodopsins have been expressed and folded into the functional holoprotein in cell free expression systems, while other microbial rhodopsins fail to properly bind the chromophore all-trans retinal as indicated by the missing visible absorption. SEIRAS experiments suggest that all investigated rhodopsins lead to the production of polypeptides, which are co-translationally inserted into a solid-supported lipid bilayer during the first hour after the in-vitro expression is initiated. Secondary structure analysis of the IR spectra revealed that the polypeptides form a comparable amount of α-helical structure during the initial phase of insertion into the lipid bilayer. As the process progressed (> 1 hour), only HsBR exhibited a further increase and association of α-helices to form a compact tertiary structure, while the helical contents of the other rhodopsins stagnated. This result suggests that the molecular reason for the unsuccessful cell-free expression of the two sensory rhodopsins and of CrChR2 is not due to the translation process, but rather to the folding process during the post-translational period. Taking our previous observation into account that HsBR fails to form a tertiary structure in the absence of its retinal, we infer that the chromophore retinal is an integral component of the compaction of the polypeptide into its tertiary structure and the formation of a fully functional protein.